Optimal tube length of orotracheal intubation for mice. (February 2019) - Nosaka, Nobuyuki; Crother, Timothy R.; Chen, Shuang; Arditi, Moshe; Shimada, Kenichi
Endotracheal tube (ETT) management is an essential technique in handling mice with mechanical ventilators. Malposition into bronchi causes not only lethal complications for them but also less efficient mechanical ventilation. However, in general, it is difficult to know whether the ETT is placed with appropriate depth into the trachea of mice. We measured the distance from incisors to the bifurcation of trachea of multiple mice, and created a new estimation formula to obtain the suitable ETT length for mice with a body weight range from 17 g to 25 g: length (mm) = 0.5 × bodyweight (g) + 7. However, millimeter step adjustments are impracticable. Thus, slightly shorter than 2 cm (18–20 mm) may be the universal ETT length for mice with bodyweight > 17 g. Furthermore, their foot size may be a good alternative to predict the individual optimal ETT length for mice.